Pengaruh model pembelajaran moody ditinjau dari motivasi belajar terhadap keterampilan menulis puisi pada peserta didik kelas V sekolah dasar - Renaningtiyas Ayu Purwadi; Slamet Slamet; Jenny Indrastoeti Siti Poerwanti (Didaktika Dwija Indria, 2019)
Abstract: This experimentation to get wind with three objectives, the first is to find out influence of the diference poetry writing skill between students that learned by Moody's lerning model and students that learned with Explicit Instruction learning model, the second is to find out influence of the differences in students who have high and low learning motivation towards poetry writing skills, the third is to find out the instraction betwen leaning model along with leaning motivation towards poetry writing skill. Population of study was all fifth grade of SD N in Bendosari region. There are 2 elementary schools as samples of research taken randomly using Cluster Random Sampling technique. The data collection technique of poetry writing skill was test techniques and learning motivation questionaire was non-test techniques in the form of questionaire. The data analysis technique used variance two-way analysis. The significance level used was 0.05. The results of the study showed that there are any effect of the differences in poetry writing skills betwen students who were taugh by Moody's learning model along with students were taugh using Explicit Instruction learning model, there are any effect of the differences in poetry writing skill between students who have high motivation and low motivation, and there is no interaction between learning model along with learning motivation towards poetry writing skill.Keyword : Moody, Explicit Instruction, Learning Motivation, Poetry Writing Skill, Elementary school